A Jesuit Poetic Doctrine: Mambrun's "Dissertatio de epico carmine" - Sánchez Manzano, María Asunción (2017)
In 1652, a time when several ancient sources and comments on Poetics were disputed, Pierre Mambrun wrote an essay, Dissertatio de epico carmine, expounding literary criteria by which to judge the flourishing genre of the French epic. This paper provides an overview of the Jesuit (Mambrun, Masen, Le Moyne, Le Brun) literary doctrine on the epic between 1650 and 1670. Mambrun discussed the definitions proposed in the main commentaries published before the impact of Boileau-Despréaux's translation of De sublimitate in 1674. After having explored the range of different definitions of the epic genre and imitation, Mambrun's contribution to a methodical analysis of Virgil's achievements is highlighted.
Keywords: Mambrun, Pierre, -- 1601-1661; Poesía épica